BIM-Based Integrated Model for Project Cost Estimation: A Case Study for Concrete Elements - Elsheikh, Asser; Saqr, Abdullah; Motawa, Ibrahim (Civil Engineering Journal, 2025)
Construction projects often struggle to align design models, cost estimates, and scheduling processes. To address this challenge, this study presents an integrated 5D BIM model that automates cost and schedule estimation by linking 3D BIM components to a structured database of historical productivity and activity data. A unique coding system connects each BIM object to its corresponding construction tasks, enabling automatic generation of resource-loaded schedules with associated durations, costs, and crews based on the selected construction method. The workflow integrates Autodesk Revit, Navisworks, a relational (SQL) database, and Primavera P6 to achieve seamless interoperability across design, estimating, and scheduling tools. The model is validated through a case study of a six-story reinforced concrete building. Findings show that the approach significantly improves estimation, accuracy, and efficiency. Predicted costs closely match actual values, thereby reducing dispersion among estimates. The automated process minimizes manual data handling while keeping cost and schedule outputs synchronized. Novel contributions include the incorporation of detailed historical productivity data, construction method alternatives, and structured cost/activity records into a unified framework, representing a methodological advance in 5D BIM that bridges the design, estimating, and scheduling domains for more reliable and automated project planning.